SR induced micro-XRF for studying the spatial distribution of Pb in plants used for soil phytoremediation. (January 2019) - Mera, M.F.; Rubio, M.; Pérez, C.A.; Cazón, S.; Merlo, M.; Muñoz, S.E.
Abstract: The phytoextraction technology uses vegetable species to extract toxic metals from contaminated soils and accumulate them in the harvestable parts of the plants, which can then be removed from site. The aim of this work was to perform a study by SR micro X-ray fluorescence technique of the spatial distribution of Pb in roots and leaves of two different species of plants potentially useful for soil phytoremediation. The experiments were conducted in Brassica napus and Festuca arundinacea . The plants were grown in Pb soil contaminated, in controlled environment, cultivated in greenhouses at CEPROCOR. The measurements were carried on at the D09B XRF Fluorescence beamline of the Brazilian Synchrotron Light Laboratory (LNLS), on different parts of the living plant. SR induced micro-XRF results showed that Brassica napus extracted Pb from the ground and translocated it to the leaves more effectively than Festuca arundinacea, grown in contaminated soil, where lead remained at the root. Furthermore, a co-distribution was observed between Pb and Zn, P, S and Fe. This suggest that Brassica napus is a potential plant to be used for phytoextraction of Pb from soil. The use of SR micro-XRF to map the distribution of metals in plant tissue allows significant advances in phytoremediation studies as well as in other topics of environmental sciences. Highlights: SR micro-XRF is an innovative technique that allows the mapping of the distribution of a wide range of elements in vegetable tissues. Phytoextraction could be an alternative technology to remove heavy metals from contaminated soils. SR micro-XRF results showed that Brassica napus extracted Pb from the ground and translocated it to the leaves. Furthermore, a co-distribution was observed between Pb and Zn, P, S and Fe. Brassica napus is a potential plant to be used for phytoextraction of Pb from soil.